Halal Tourism in Indonesia: Challenges of Fairness in Policy Implementation - Diana Novita; Dewi Novitasari; Aditya Maulana Rizqi (Soedirman Law Review, 2024)
Indonesia, with the world’s largest Muslim population, holds strong potential for developing halal tourism. However, inconsistent regulation across regions creates inequalities that limit fair and sustainable growth in this sector. This study aims to address a gap in the literature by analyzing how uneven regulation impacts destination competitiveness and the distribution of economic benefits. Using a qualitative, descriptive approach, this research examines regulatory implementation through case studies in diverse regions, highlighting local factors causing disparity, such as institutional capacity, government support, and public awareness. Findings reveal that the absence of a cohesive national policy on halal tourism results in regulatory imbalances, with local differences in capacity and support affecting outcomes. This study underscores the need for a more inclusive national policy to ensure fair economic distribution and promote sustainable halal tourism throughout Indonesia. By offering a fresh equity-based perspective on the implementation of halal tourism regulations, this research provides a valuable contribution to existing literature on the subject.Keywords: Halal; Tourism; Regulation.